MRAS-based sensorless control for high-speed induction machine connected to the grid - Lima, Fabio; Camargo Rosa, Fabiano; Fumagalli, Marco Antonio (IECON 2013 - 39th Annual Conference of the IEEE Industrial Electronics Society, 2013)
This paper describes a MRAS-based sensorless control of a high-speed squirrel cage induction machine connected to the grid. This paper contributes with the subject when using a high-speed machine supported by active magnetic bearings (AMB) for energy applications. This kind of system is suitable for energy generation from gas sources. To control the grid side as well as the generator side a back-to-back converter with voltage oriented control (VOC) and rotor field oriented control (RFOC), respectively, is used. Simulations are presented for the MRAS observer, and some experimental results are also showed. A test bench was designed and the final experimental results are undergoing.